Adansonia digitata (Baobab) fruit pulp as substrate for Bacillus Endoglucanase production - Ibrahim, A.D.; Mukhtar, Sa’adat I.; Ibrahim, M.N.; Oke, M. A.; Ajijolakewu, A.K (Research in Biotechnology, 2012)
In recent years the cost of carbon source for microbial enzymes production has necessitated a drive towards cheaper and sustainable sources. In this study, Adansonia digitata (Baobab) fruit pulp was utilized as substrate for Bacillus endoglucanase production and the effects of varying temperature, pH, incubation period, inoculum size and substrate concentration on endoglucanase production were investigated. The cellulolytic activity of the isolates was screened base on halo of clearance on CarboxymethylÃ‚Â cellulose agar, while the endoglucanase activity of the selected Bacillus species was monitored using 3, 5 - dinitrosalicylic acid (DNS) method. Out of 4 Bacillus species screened, only Bacillus amyloliquefaciens and Bacillus subtitis showed cellulolytic activity with B. amyloliquefaciens having the highest activity of 20.0 mm. Therefore B. amyloliquefaciens was selectedÃ‚Â for studies on the effect of fermentation conditions on endoglucanase activity. The maximum yield of endoglucanase was produced at temperature of 55 oC, pH 2, 1% inoculum size and 1% substrate concentration for 4 days incubation period. The results of this studyÃ‚Â suggest that Adansonia digitata fruit pulp can be harnessed at low concentration for large scale endoglucanase production by Bacillus, and the endoglucanase produced by B. amyloliquefaciens could be a thermostable enzyme with novel characteristics suitable for application in biofuel and textile industry.